Bank CEO incentives and the credit crisis - Fahlenbrach, Rüdiger; Stulz, René M. (Journal of Financial Economics, 2011)
We investigate whether bank performance during the recent credit crisis is related to chief executive officer (CEO) incentives before the crisis. We find some evidence that banks with CEOs whose incentives were better aligned with the interests of shareholders performed worse and no evidence that they performed better. Banks with higher option compensation and a larger fraction of compensation in cash bonuses for their CEOs did not perform worse during the crisis. Bank CEOs did not reduce their holdings of shares in anticipation of the crisis or during the crisis. Consequently, they suffered extremely large wealth losses in the wake of the crisis.